Implementation of the Entrepreneurship-Based Vocational Skills Learning Model Through P5 Activities at SLB ABD Kedungkandang Malang - Ummah, Umi Safiul; Riswari, Fina; Binti Yahya, Amira Najiha; Viorella, Nanda; Salsabila, Naurah; Nur Azizah, Berlianti Apriliana (Universitas Negeri Malang, 2024)
This research aims to describe the implementation of an entrepreneurship-based vocational skills model through the Strengthening Pancasila Student Profile (P5) Project activities with the theme of entrepreneurship. The research method used is qualitative approach with descriptive research. The research subjects were 6 interviewees which include the school principal, deputy principal for curriculum, teachers of class IV, VII, and VIII. Data source include primary data with data collection include observation, interviews and documentation. Data then analyzed using the Miles and Huberman model. The results of the research showed that the implementation of entrepreneurship- based vocational learning through P5 activities in classes IV, VII, and VIII of SLB ABD Negeri Kedungkandang is carried out in accordance with the context to increase independence and foster an entrepreneurial spirit in students. Besides, students also have a high enthusiasm in its implementation. The implementation of P5 can increase the entrepreneurial spirit and cooperation between students with special needs.